An inpatient antimicrobial stewardship team driven penicillin allergy delabeling protocol for minimal and low-risk penicillin allergic patients - Shivanjali Shankaran; Emily Adochio; Robert Petrak; Benjamin Goldenberg; Fischer Herald; Christy Lunn; Hayley Hodgson; Sarah Won (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Inappropriate penicillin allergy labeling results in suboptimal or excessive broad spectrum antibiotic use. In this multidisciplinary project, the antimicrobial stewardship team safely delabeled 71.4% of hospitalized patients approached. Similar programs may also be able to delabel minimal or low-risk penicillin allergic patients without formal allergy consultation.